2007
DOI: 10.1111/j.1745-4514.2007.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of the Proline-Linked Pentose Phosphate Pathway Metabolites and Antioxidant Enzyme Response by Ascorbic Acid in Dark Germinated Fava Bean Sprouts

Abstract: Elicitation by ascorbic acid stimulated higher phenolic content in late stages of germination and higher antioxidant activity during early and late germination in fava bean sprouts. The high free radical scavenging‐linked antioxidant activity on day 1 coincided with high levo‐dihydroxy phenylalanine and total phenolics. A positive correlation between the stimulation of phenolic synthesis and glucose‐6‐phosphate dehydrogenase (G6PDH) activity was also observed, indicating its likely role in carbohydrate mobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
2
5
0
Order By: Relevance
“…However, the application of ascorbic acid, folic acid or chitosan/glutamic acid enhanced significantly (P ≤0.05) the phenolic content in sprouted lentils (3.6-3.9 mg GAE/g d.w.) and no significant differences (P>0.05) among these elicitors were found. Our results are in agreement with those reported for sprouted peas, fava beans and kidney beans [14][15][16]19]. The increased TPC concentration found in elicited sprouted lentils could be attributed to de novo synthesis of phenolic compounds since previous studies observed that chitosan and ascorbic and folic acids stimulate the pentose phosphate and phenylpropanoid pathways in legumes [14,16].…”
Section: Content Of Total Phenolic Compounds (Tpc) In Elicitedsupporting
confidence: 95%
See 2 more Smart Citations
“…However, the application of ascorbic acid, folic acid or chitosan/glutamic acid enhanced significantly (P ≤0.05) the phenolic content in sprouted lentils (3.6-3.9 mg GAE/g d.w.) and no significant differences (P>0.05) among these elicitors were found. Our results are in agreement with those reported for sprouted peas, fava beans and kidney beans [14][15][16]19]. The increased TPC concentration found in elicited sprouted lentils could be attributed to de novo synthesis of phenolic compounds since previous studies observed that chitosan and ascorbic and folic acids stimulate the pentose phosphate and phenylpropanoid pathways in legumes [14,16].…”
Section: Content Of Total Phenolic Compounds (Tpc) In Elicitedsupporting
confidence: 95%
“…This statement is supported by the positive correlation (r=0.75) found between TPC content and ORAC values. Our results are consistent with previous studies indicating that abiotic elicitors increased the phenolic content and, consequently, the antioxidant activity of vegetable sprouts [14][15][16]. Ascorbic acid is a potent natural antioxidant that might also contribute to the enhancement of ORAC values in lentil sprouts treated with this elicitor, as it has been previously observed in pea sprouts [14].…”
Section: Content Of Total Phenolic Compounds (Tpc) In Elicitedsupporting
confidence: 95%
See 1 more Smart Citation
“…authors have indicated the positive correlation between phenol synthesis and activities of glucose 6-phosphate dehydrogenase which stimulates mobilization of sugars to phenylpropanoid pathway (Randhir & Shetty 2007). Our results showed that biostimulant in conditions of reduced NPK nutrition can affect the ratio of total sugars and acids, but the change of these two parameters is specific for particular genotype (Figure 1).…”
Section: Fruit Quality Parametersmentioning
confidence: 48%
“…The obtained results in our research showed positive correlation between increase of fruit ascorbic acid content, TPC in the leaves, as well as TAC (Figure 1(c) and Figure 2) and a similar trend was obtained in some other research studies (Parađiković et al 2011; Zodape et al 2011). According to literature data, increased content of ascorbic acid is closely associated with phenol concentration due to stimulation of phenylpropanoid pathway, whereby antioxidative capacity also increases (Randhir & Shetty 2007).…”
Section: Leaf Antioxidative Capacity and Phenol Contentmentioning
confidence: 99%